KARAKTERISTIK METODE TAFSIR AL-QURAN UNTUK ANAK: STUDI TAFSIR JUZ ‘AMMA FOR KIDS KARYA ABDUL MUSTAQIM - Luthviyah Romziana; Fika Khoirina Axmaliyatus Syamsyiah (Al-ATHFAL: Jurnal Pendidikan Anak, 2025)
The study aims to examine the systematics and methodology of Quranic interpretation for children in Tafsir Juz 'Amma for Kids by Abdul Mustaqim and to analyze the advantages and disadvantages of this interpretation. The research employs a qualitative method with a content analysis approach. The primary data used in this study is Abdul Mustaqim's Tafsir Juz 'Amma for Kids. While the secondary data comes from various literature, both from books and journals related to interpretation methods and child development psychology. The results show that the interpretation method used is the tahlili method with a systematic structure, beginning with the introduction, asbabun nuzul (when available), vocabulary, general interpretation, and conclusion. The main characteristics of this interpretation include the use of simple and communicative language, a narrative style that is easy for children to understand, and is equipped with visual illustrations to strengthen understanding. The advantages of this interpretation lies in its child-friendly and structured approach, while its disadvantages are the limited coverage of surah, the lack of guidance for facilitators, and the suboptimal digital visual aspect. This research contributes to the development of contextual and relevant interpretations for children, and can be used as a reference by teachers and parents in assisting children in learning the Qur'an. Keywords: Abdul Mustaqim; Juz 'Amma for Kids; Interpretation Method; Children's Interpretation